The Role of OxyR and SoxRS in oxidative stress survival in Shigella flexneri - Daugherty, Aaron (2011)
Shigella flexneri, a facultative intracellular pathogen, is exposed to a variety of environments inside and outside of the human host. Some of these environments may contain significant oxidative stress. S. flexneri mutants were generated with deletions in the major oxidative stress regulators oxyR and/or soxRS to test their importance in Shigella biology. Strains that contained a deletion of oxyR had reduced growth and survival during aerobic growth, but not microaerobic growth. The mutants were also defective in surviving exposure to oxidative stress: oxyR mutants were sensitive to hydrogen peroxide, while soxRS mutants were sensitive to superoxide. Although the ΔsoxRS, ΔoxyR, and ΔoxyR/ΔsoxRS mutant Shigellae survived similarly to the parental strains within macrophages, the mutants formed plaques on Henle cell monolayers that were slightly smaller than the plaques formed by the wildtype strain.